Fish and Fish Resources in the Mangrove Swamps of Sundarbans, West Bengal-an Indepth Study - Chakrabarti, Kalyan (Indian Forester, 1986)
The organisation of a rational fishery in the Sundarbans Mangrove swamps holds bright promise to boost the economy of West Bengal. Scientific exploitation of fish resources is an economic proposition. This study identifies the optimum time and place of fishing and other conditions to ensure high productivity of fish populations. The paper also describes the ecology of fish species and silvo-pisciculture aspect of the mangrove swamps, and quantifies the fish catch in brackish water fisheries.